Pengaruh Inflasi, Infrastruktur Digital, dan Keamanan Siber terhadap Pendapatan E-Commerce di Negara Berkembang 2023-2024 - Asni Angelina; Sri Indah Nikensari; Siti Fatimah Zahra (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effect of inflation, digital infrastructure, and cybersecurity on e-commerce revenue in developing countries during the 2023-2024 period. This study employed a quantitative approach using secondary data from 62 developing countries selected through purposive sampling. The data were analyzed using panel data regression with the Fixed Effect Model (FEM) approach. The results indicate that inflation has a negative and significant effect on e-commerce revenue, meaning that every 1% increase in inflation reduces e-commerce revenue by 4%. Digital infrastructure has a positive and significant effect on e-commerce revenue, where a 1% increase in digital infrastructure increases e-commerce revenue by 64%. Cybersecurity also has a positive and significant effect, with a 1% increase in cybersecurity leading to a 3% increase in e-commerce revenue. The coefficient of determination (R²) of 0.9978 indicates that the three independent variables are able to explain 99.78% of the variation in e-commerce revenue, while the remaining 0.22% is explained by other factors outside the model. The findings of this study confirm that controlled inflation, adequate digital infrastructure, and strong cybersecurity are key factors in encouraging the growth of e-commerce revenue in developing countries.